2013
DOI: 10.5539/gjhs.v5n4p1
|View full text |Cite
|
Sign up to set email alerts
|

HIV Disclosure to Partners and Family among Women Enrolled in Prevention of Mother to Child Transmission of HIV Program: Implications for Infant Feeding in Poor Resourced Communities in South Africa

Abstract: The introduction of routine HIV counselling and testing (HCT) has increased the number of pregnant women being tested and receiving prevention of mother to child transmission of HIV (PMTCT) interventions in South Africa. While many women may enroll in PMTCT, there are barriers that hinder the success of PMTCT programmes. The success of the PMTCT is dependent on the optimal utilization of PMTCT interventions which require the support of the woman's partner, and other members of her family. We conducted focus gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 34 publications
10
57
0
2
Order By: Relevance
“…Barriers to male involvement Madiba, et al (2013), discovered that disclosure of HIV sero-status to a partner is always the main gate to progress in PMTCT uptake and that is what pregnant women in Sub-Saharan Africa do not have confidence to do, due to the fear of negative reactions they will face from their husbands and relations. A study carried out by Bajunirwe et al (2005) in rural and urban Uganda found that women refused HIV testing in antenatal clinic due to fear of their husbands" reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Barriers to male involvement Madiba, et al (2013), discovered that disclosure of HIV sero-status to a partner is always the main gate to progress in PMTCT uptake and that is what pregnant women in Sub-Saharan Africa do not have confidence to do, due to the fear of negative reactions they will face from their husbands and relations. A study carried out by Bajunirwe et al (2005) in rural and urban Uganda found that women refused HIV testing in antenatal clinic due to fear of their husbands" reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that HCWs are likely to give adapted messages based on what they believe to be the best feeding choice for mothers (Tijou-Traore et al, 2009;Wachira et al, 2009;Madiba et al, 2013). For example, some studies have found that EFF was suggested for women of high socio-economic status while EBF was recommended for mothers of low socio-economic status (Koricho et al, 2010;Chinkonde et al, 2012).…”
Section: Content Of Healthcare Worker-provided Infant Feeding Counselmentioning
confidence: 99%
“…In addition, the timing for infant feeding counselling should be considered carefully and not given for example at the time of a new HIV diagnosis (Doherty et al, 2006a;Leshabari et al, 2006). Furthermore, mothers may receive inconsistent information or advice on infant feeding practices from various HCWs in different departments within the same health facility (Doherty et al, 2006a;Chisenga et al, 2011;Chinkonde et al, 2012;Madiba et al, 2013).…”
Section: Mixed Messages On Infant Feedingmentioning
confidence: 99%
“…Quanto à categoria suporte social emocional, observaram-se como fontes a família, 12,14,15,24,25,[27][28][29] o companheiro, 10,22,26 os amigos 15,24,27 e a crença em Deus e a fé, 15,24,27 como estímulos para continuidade do tratamento. Fica explícito que as questões culturais e familiares influenciaram nas decisões em relação aos cuidados de saúde maternos e infantis.…”
Section: Fontes E As Repercussões Do Suporte Social Emocionalunclassified
“…Conforme os estudos, 12,14,25,28 as gestantes acreditavam que os familiares apresentavam opiniões e percepções negativas acerca das pessoas com HIV, o que poderia gerar estigma e discriminação.…”
Section: Fontes E As Repercussões Do Suporte Social Emocionalunclassified